“Bumil Temker” Ibu Hamil Tempel Stiker P4k - Raudhatul Hasanah; Putri Yuliantie; Sariyati Sariyati; Ika Friscila (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The coverage rate of repeat visits for pregnant women's examinations (K4) is an indirect indicator of maternal mortality, but it can indicate the extent of access or reach to maternal health services and illustrate the opportunity to detect and treat high-risk pregnant women. Based on findings in the community, it was found that the implementation of the Childbirth Planning and Complication Prevention (P4K) Program with Stickers had not been achieved. Some pregnant women had not attached stickers and did not understand the importance of P4K stickers and the implementation of the P4K program. This Community Service Activity is in the form of a "BUMIL TEMKER" program for pregnant women to attach P4K stickers by providing education to pregnant women about their obligations and supporting the attachment of P4K stickers for pregnant women. This community service activity was carried out on September 25, 2024 in the working area of ​​the Lanjas Muara Teweh Health Center UPTD. The results of the delivery of the material provided related to the importance of implementing the Childbirth Planning and Complication Prevention (P4K) program with these stickers were an increase in the active role of husbands, families and communities in planning safe deliveries and preparing for complications for pregnant women